2012
DOI: 10.1177/1745691612437597
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Sleep, Fragmented Mind

Abstract: In psychopathology, dissociation typically refers to a disturbance in the normal integration of thoughts, feelings, and experiences into consciousness and memory. In this article, we review the literature on how sleep disturbances relate to dissociative symptoms and memory failure. We contend that this body of research offers a fresh perspective on dissociation. Specifically, we argue that dissociative symptoms are associated with a labile sleep-wake cycle, in which dreamlike mentation invades the waking state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 134 publications
6
48
1
Order By: Relevance
“…Thus, traumatic experiences may disrupt sleep, which in turn may contribute to or exacerbate dissociative symptoms. In our recent review, we (14) concluded that data from 23 studies of clinical and non-clinical samples provide strong support for a link between dissociative experiences and sleep problems. This link is evident across a range of sleep-related phenomena, including waking dreams, nightmares, and hypnagogic (occurring while falling asleep) and hypnopompic (occurring while awakening) hallucinations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, traumatic experiences may disrupt sleep, which in turn may contribute to or exacerbate dissociative symptoms. In our recent review, we (14) concluded that data from 23 studies of clinical and non-clinical samples provide strong support for a link between dissociative experiences and sleep problems. This link is evident across a range of sleep-related phenomena, including waking dreams, nightmares, and hypnagogic (occurring while falling asleep) and hypnopompic (occurring while awakening) hallucinations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, stress and worry carry prolonged cardiovascular effects into sleep, independent of sleep quality, which have been labeled “unconscious worry” (Brosschot et al, 2007). Importantly, some individuals seem to be especially capable of lingering in mixed sleep-wake states, including dissociative experiences and parasomnias (Mahowald and Schenck, 2001; Giesbrecht et al, 2008; Koffel and Watson, 2009; van der Kloet et al, 2012b). Dissociation and GSEs may reflect a reciprocal process in which sleep and waking intrude into one another.…”
Section: Gses As Disrupted Sleepmentioning
confidence: 99%
“…The link between sleep problems and diminished coping in the face of traumatic stress is further supported by findings that sleep problems are also associated with trauma-related dissociative symptoms (van der Kloet, Merkelbach & Giesbrecht, 2012). In addition to PTSD and mood disturbance, future longitudinal studies of trauma-related sleep problems should examine other forms of distress such as paranoia, hostility, and obsessive-compulsive symptoms that are potentially exacerbated by trauma and resource loss.…”
Section: Discussionmentioning
confidence: 87%